Pathogenic and periodontal bacteria may contribute to the fatal outcome of critically ill elderly COVID-19 patients - L. Johana Madroñero; Eliana P. Calvo; Carolina Coronel-Ruiz; Myriam L. Velandia-Romero; María Angélica Calderón-Peláez; Jhann A. Arturo; Adriana P. Franco-Rodríguez; Ricardo Gutiérrez-Pérez; Lady S. López; Félix G. Delgado; Sigrid J. Camacho-Ortega; Lilia J. Bernal-Cepeda; et al. (Scientific Reports)
Abstract Some studies suggest that the respiratory microbiome of COVID-19 patients differs from that of healthy individuals, infected patients may have reduced diversity and increased levels of opportunistic bacteria, however, the role of the microbiome in fatal SARS-CoV-2 infection remains poorly understood. Our study aimed to determine whether there are differences in the respiratory microbiome between patients who recovered from COVID-19 and those who died, by characterizing the bacterial communities of both groups. A total of 24 patients who recovered from COVID-19 and 24 who died were included in the study, patient data were analyzed for signs, symptoms and clinical variables. Airway samples were collected and the 16 S rRNA variable regions V3-V4 were amplified and sequenced using the Illumina MiSeq platform. Elevated levels of blood urea nitrogen, creatinine and lactate dehydrogenase, and higher frequencies of cardiovascular disease, diabetes mellitus and renal disease were observed in patients with a fatal outcome. Compared to patients who recovered from COVID-19, patients who died exhibited a microbiome enriched in periodontal and pathogenic bacteria such as Klebsiella pneumoniae. Our results highlighted a dual relationship between SARS CoV-2 infection and an exacerbated periodontopathogen-induced immune response.